(untitled) (Journal of International Studies, 2020)
The book comprehensively outlines the history of marine fisheries in Southeast Asia from the period of the late nineteenth century to the start of the twenty first century. The greatest value of this book lies on its central theme of discussion that sets apart from other historical literature on marine fisheries. Instead of studying on the general history of marine fisheries, the central theme of the book highlights the movements of fishing grounds in the region’s oceanic waters. Based on long and extensive research stretching over 11 years, the focus of the book is on the historical aspect of captured marine fisheries. The author chooses the year 1850 as his starting point of discussion. His selection of periods is justified due to the lack of available historical literature and other written sources on regional fisheries prior to that particular period.